To earmark or not to earmark? : a far-reaching debate on the use of auction revenue from (EU) emissions trading - Müller, B (Oxford Institute for Energy Studies, 2008)
Should revenue from auctioning of emission permits in the EU Emission Trading Scheme (ETS) be earmarked −'hypothecated'− for funding climate change activities, particularly in developing countries?